Analisis Etika Komunikasi Pada Konten Viral di Media Sosial Tik-Tok - Indah Cahya Mentari; Eko Prasetyo Nugroho Saputro; Arum Widayanti (Program Studi Komunikasi dan Penyiaran Islam, 2024)
This research is motivated by the importance of upholding ethics on social media. This research aims to explore the perceptions and reactions of viewers, as well as the factors influencing these perceptions and reactions, towards the communication ethics of viral live-streaming content on TikTok @imeyhou (Meyden). Utilizing a qualitative approach, this study employed a case study method. Data were collected through interviews, observations, and documentation techniques. The informants in this research were viewers of @imeyhou (Meyden)’s live-streaming content. The results indicate that viewers' perceptions and reactions to the communication ethics of Meyden's viral live-streaming content are varied, with many expressing concerns due to frequent impolite words. Consequently, viewers tend to limit their exposure to and avoid Meyden’s live-streaming content and similar content. The factors influencing viewers' perceptions and reactions to communication ethics in this context are varied. Internal factors include individual attitudes, personalities, and values. External factors encompass the information received and the knowledge possessed by the viewers. The information about Meyden’s live streams is predominantly negative, primarily due to the frequent use of swear words, which fosters a negative perception of communication ethics. Viewers' reactions are influenced by three main variables: attention, understanding, and acceptance.